Bodybuilding the complete contest preparation handbook - Fitschen, Peter J. 1986-; Wilson, Cliff 1984- (Human Kinetics, 2020)
"The purpose of this book is to provide a comprehensive overview of the bodybuilding contest preparation process from the start of contest preparation, through show-day, and into the transition to the offseason"--Provided by publisher.